Wild data: how front‐line hospital staff make sense of patients' experiences. Issue 6 (31st May 2020) - Montgomery, Catherine M.; Chisholm, Alison; Parkin, Stephen; Locock, Louise
Abstract: Patient‐centred care has become the touchstone of healthcare policy in developed healthcare systems. The ensuing commodification of patients' experiences has resulted in a mass of data but little sense of whether and how such data are used. We sought to understand how front‐line staff use patient experience data for quality improvement in the National Health Service (NHS). We conducted a 12‐month ethnographic case study evaluation of improvement projects in six NHS hospitals in England in 2016–2017. Drawing on the sociology of everyday life, we show how front‐line staff worked with a notion of data as interpersonal and embodied. In addition to consulting organisationally sanctioned forms of data, staff used their own embodied interactions with patients, carers, other staff and the ward environment to shape improvements. The data staff found useful involved face‐to‐face interaction and dialogue; were visual, emotive, and allowed for immediate action. We draw on de Certeau to re‐conceptualise this as 'wild data'. We conclude that patient experience data are relational, and have material, social and affective dimensions, which have been elided in the literature to date. Practice‐based theories of the everyday help to envision 'patient experience' not as a disembodied tool of managerialism but as an embedded part of healthcare staff professionalism.